Stabilization of monocyte chemoattractant protein-1-mRNA by activated protein C - Brückmann, Martina; Marx, Antje; Weiler, Hans-Martin; Liebe, Volker; Lang, Siegfried; Kaden, Jens; Zieger, Wolfgang; Borggrefe, Martin; Huhle, Günter; Haase, Karl Konstantin (Thrombosis and haemostasis, 2003)
The activated protein C (APC) pathway has been suggested to be a common link between coagulation and inflammation. APC may function to restore hemostasis via modulation of cytokine expression. We investigated the effect of APC on the endothelial expression of monocyte chemoattractant protein-1 (MCP-1), a chemokine that is controlled by the activation of central proinflammatory transcription factors, such as nuclear factor-kappa B (NF-κ B). - - We found that human APC (2.5-10 μ g/ml) upregulated the amount of MCP-1-mRNA in human umbilical vein endothelial cells (HUVEC) and caused a time- and dose-dependent increase in MCP-1 protein production (p The ability of APC to upregulate the production of MCP-1, most likely by increasing the stability of MCP-1-mRNA rather than by transcriptional activation via NF- B, identifies a novel immunomodulatory pathway, by which APC may control the local inflammatory reaction, thereby initiating wound repair and modulating the extent of endothelial injury.
Elektronische Reproduktion der Druck-Ausgabe
Publikationsdatum: 09. Dezember 2017 (online)
Gesehen am 23.06.2022